UPAYA PENINGKATAN HASIL BELAJAR KOGNITIF MATEMATIKA MELALUI PENDEKATAN TEORI BELAJAR BRUNER BAGI SISWA KELAS II MADRASAH IBTIDAIYAH CITAMIANG LAKBOK CIAMIS - Rita Lestari; Dodo (Jurnal Garasi Buku dan Obrolan Keilmuan, 2023)
Mathematics subjects are given since Elementary School/Madrasah Ibtidaiyah at the formal school level. Based on the 2013 Elementary School Content Standards, Mathematics is considered a universal science that will be used as the basis for the development of other sciences. Therefore, for a solid mastery of this knowledge is given early. This research is classroom action research. This research is intended to improve the learning process so that it can improve the cognitive learning outcomes of Mathematics for second graders of MI Citamiang Lakbok. According to Suharsimi Arikunto (2006: 96) classroom action research, namely research conducted by the teacher to the class where he teaches with an emphasis on improving learning processes and practices. Research activities carried out in two cycles. Each cycle is carried out in two meetings. Before carrying out the cycle, the researcher carried out pre-action activities. The process of learning mathematics in class II MI Citamiang Lakbok has increased from only presenting counting techniques to being preceded by concepts. In addition, students are more active in learning activities. The cognitive learning outcomes of MI Citamiang Lakbok class II students also increased. In pre-action only 43% reached KKM. Furthermore, in cycle one it increased to 52% and in cycle two it increased again to 76%. Teachers must better understand how to convey material to students according to the level of student development. BIBLIOGRAPHY Ahmad Susanto. (2014). Teori Belajar dan Pembelajaran di Sekolah Dasar/Madrasah Ibtidaiyah. Jakarta: Kencana BSNP. 2006. Standar Isi SD/MI. Jakarta: BSNP. Purwanto. (2010). Evaluasi Hasil Belajar. Yogyakarta: Pustaka Pelajar. Ritta Eka Izaty. 2012. Perkembangan Peserta Didik. Yogyakarta: UNY Press. Sudrajat. 2008. Peranan Matematika dalam Perkembangan IPTEK. Artikel disampaikan dalam seminar The Power of Mathematics in All Application. Suharsimi Arikunto. (2006). Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta: PT. Rineka Cipta. Sugihartono. 2012. Psikologi Pendidikan. Yogyakarta: UNY Press. Zulkifar Ali Buto. 2010. Implikasi Teori Belajar Jerome Bruner Dalam Nuansa Pendidikan Modern. Jurnal Millah Edisi Khusus Desember 2010 halaman 55-69.